Resolution of cryptosporidiosis with probiotic treatment. Issue 940 (17th February 2004) - Pickerd, N; Tuthill, D
Abstract : Cryptosporidium infection is usually self limited, but can be a life threatening illness in immunocompromised patients. Probiotics have been used successfully in the treatment of acute diarrhoea and they have also been shown to limit Cryptosporidium parvum infection in animal models. The first case of successful resolution of prolonged cryptosporidiosis with probiotic treatment is reported.